Лінгвістичний контекст моделювання військового конфлікту на основі сценаріїв - Федорчук, Євдоким; Шайда, Оксана; Шокур, Євген (Видавництво Львівської політехніки, 2015)
The paper presents an approach to the choice of data structures for representation of the linguistic context of military conflict. The technology of computer modelling of the conflict scenario is viewed.
Keywords: військовий конфлікт; модель сценарію; лінгвістичний контекст